(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
Equivalent continuous sound pressure level LAeq is the main variable characterizing the physiological effects of noise on humans. The technological equipment for woodworking and furniture industry includes the woodworking milling machines, which at the same time are characterized with high levels of noise emissions. The current study investigates the changes in equivalent sound pressure level measured at workplace during milling of details from common beech wood (Fagus Sylvatika L). The influence of the construction and rotational speed of the cutting tool have been studied. It was found that depending on the cutting speed and the construction characteristics of the cutting tool, the equivalent sound pressure level LAeq for eight hour working day varies from 74 dB(A) tо 89 dB(A).